The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1039/c3cp51441b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of NO2 storage in ceria studied using combined in situ Raman/FT-IR spectroscopy

Abstract: In situ Raman spectroscopy combined with quantitative FT-IR gas phase analysis was used to elucidate the mechanism of NO2 storage in ceria. At room temperature, NO2 exposure induces an immediate increase in the degree of ceria reduction accompanying nitrate formation. Two parallel reaction pathways for nitrate formation are identified. The presence of steam strongly influences the storage behavior by favoring the formation of free nitrates over bidentate/bridging nitrates. At 200°, faster free nitrate formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 31 publications
5
30
0
Order By: Relevance
“…Initial stages of 14 NO/ 15 NO interaction with reduced ceria. It is also seen that with the two samples the bands appear with strongly different relative intensities.…”
Section: Initial Characterization Of the Samples And Background Spectramentioning
confidence: 99%
See 3 more Smart Citations
“…Initial stages of 14 NO/ 15 NO interaction with reduced ceria. It is also seen that with the two samples the bands appear with strongly different relative intensities.…”
Section: Initial Characterization Of the Samples And Background Spectramentioning
confidence: 99%
“…It was demonstrated [21] that bands at 1270 and 1160 cm -1 (assigned to chelating nitrites) and a band at 1090 cm -1 (attributed to trans-hyponitrites) were due to N-O modes because were accordingly shifted after adsorption of 15 NO. Szanyi and Kwak [50] recently reported that 15 nitrite species (1153 and 815 cm -1 ) absorb at 1137 and 798 cm -1 after substitution of one of the 16 O atoms by 18 O. It is established that the deNO x activity of ceria correlates with the number of oxygen vacancies [17].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, we have shown that nickel sulfides can be formed during cooling at the end of the experiment. Since in situ Raman spectroscopy has proved to be able to characterize electrode reactions in SOFCs and H 2 S reaction products , , , as well as adsorbed species , we combined electrochemical measurements with in situ Raman spectroscopy to monitor cell evolutions under open circuit and polarizing conditions at 500 °C.…”
Section: Introductionmentioning
confidence: 99%